Web-Based Patient Clinical Data Information System at Clinic Pratama - Suryadi, Agung; Nurhayati, Nurhayati; Sihotang, Marco Lukisla Nikato; Pertiwi, Athica Cytra (Global Health Science Group, 2024)
The existence of information technology has now had a major influence in all fields, including the health sector. The application of information technology can be used as a solution in managing health data. One example is designing a system for registering and filling in patient clinical data at Pratama clinics. In general, the implementation of health data processing still uses manual methods which has problems from distribution officers, namely if a medical record file is missed, so it takes time to search for medical records. The research method used is a descriptive survey. The data collection method is observation and free guided interviews. By identifying outpatient registration flow variables, patient data, registration data, doctor data, examination data and polyclinic data. The approach used is cross sectional. And uses a system development method, namely SDLC (System Development Life Cycle). The design of a website-based clinical data filling information system at Pratama Clinic was built using the PHP programming language and MYSQL database with input of patient data, registration data, doctor data, examination data and polyclinic data. Then it produces output patient data reports, registration data reports, doctor data reports, polyclinic data reports, KIB, and daily patient examination reports